2013
DOI: 10.1002/met.1441
|View full text |Cite
|
Sign up to set email alerts
|

Analysing motives behind willingness to pay for improving early warning services for tropical cyclones in Vietnam

Abstract: Pressure on government budgets has made it more important to quantify the value of public goods, e.g. tropical cyclone warning services, to society as a whole. Based on a stated preference survey, in which respondents could indicate the amount of their willingness to pay (WTP), this study elicited values for an improved cyclone warning service in Vietnam. To examine motives or reasons behind respondents' WTP, respondents were requested to allocate 10 points among different types of values, including self-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Analysis of WTP in the TEWS management uses several variables, namely age, education level and income. This is consistent with Asgary, Levy, & Mehregan (2007) and Nguyen & Robinson (2015) who use these variables in determining WTP estimates for early warning management against natural disasters.…”
Section: Wtp Tsunami Early Warning Systemsupporting
confidence: 86%
“…Analysis of WTP in the TEWS management uses several variables, namely age, education level and income. This is consistent with Asgary, Levy, & Mehregan (2007) and Nguyen & Robinson (2015) who use these variables in determining WTP estimates for early warning management against natural disasters.…”
Section: Wtp Tsunami Early Warning Systemsupporting
confidence: 86%
“…The stated preference method has been widely used for estimating the economic value of public goods or services. It has also been used in the valuation of climatic and meteorological information, using both contingent valuation [5,8,9,11,23] and choice experiments [6]. The contingent valuation method attempts to measure the value that people place on a particular public good or service taken as a specific bundle of attributes [31].…”
Section: The Stated Preference Methodsmentioning
confidence: 99%
“…The use of choice experiments is relatively new for the non-market valuation of climatic and meteorological information, and very few choice-experiment studies have been undertaken. Nguyen et al [6] is the only study that we found using a choice experiment to examine climatic and meteorological information. They estimated the benefits of an improved cyclone warning service to households in Vietnam.…”
Section: The Stated Preference Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the authors found a mean WTP of $4.36 per household for improvements in landfall time forecasts, but willingness to pay only $1.30 for improvements in wind-speed forecasts. Other more specific forecasts that have been valued include climate forecasts in Benin (Amegnaglo et al 2017), improvements in tropical cyclone forecasts in Vietnam (Nguyen and Robinson 2015), and improvements in forecasts for agricultural producers in Italy (Predicatori et al 2008). Nguyen and Robinson (2015) relied on a national sample of 863 Vietnamese residents and a choice experiment attempting to value various aspects of cyclone forecasts including accuracy, number of updates, and mobile phone messages.…”
Section: Valuing Specific Forecast Typesmentioning
confidence: 99%